Analisis Pemahaman Konsep dan Implementasi Matematika Pada Pembelajaran Daring di SD Negeri Lolong - Nur Azizah (Jurnal Kualita Pendidikan, 2021)
The purpose of this study was to analyze the understanding and implementation of mathematics during the COVID-19 pandemic for students at the Lolong State Elementary School, Pekalongan Regency. The research method used is descriptive qualitative, to provide an overview of students' understanding of mathematical concepts during the COVID-19 pandemic at the school. Data collection techniques using questionnaires, observations, and interviews. The population in this study were 65 elementary school students and 5 classroom teachers. The indicators from the questionnaire distributed are statements about the level of understanding and implementation of mathematics for elementary school students during the COVID-19 pandemic which are grouped into 5 categories, namely solving mathematical problems, mathematical communication, mathematical reasoning, mathematical connections, and mathematical representations known as literacy. mathematics. The understanding and implementation of mathematics for students at the Lolong State Elementary School in online learning during the COVID-19 pandemic is on average very low due to various obstacles. The most prominent of them are the limited interaction between students and teachers, the limitations of online learning support tools, and the low motivation of students to learn. Therefore, small group tutoring at students' homes with limited duration and strict health protocols might be an option in the hope of reducing the low understanding and implementation of mathematics.